Putting Alternate Wetting and Drying (AWD) on the map, globally and nationally - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Working in partnership with national research institutions, IRRI has developed the Alternate Wetting and Drying (AWD) rice management practice. The practice reduces water use by up to 30% and methane emissions by 48% without impacting yield. With efficient nitrogen use and application of organic inputs to dry soil, the practice can reduce emissions even further, enhance nutrient efficiency, and deter insect infestation. AWD has been field tested and validated by rice farmers in Bangladesh, Indonesia, Lao PDR, Philippines, Myanmar, and Vietnam. AWD is now being mainstreamed in extension efforts by formal extension institutes and NGOs in a number of countries in Southeast Asia. Training and extension materials on AWD are also being included in curricula of agricultural colleges, universities and extension certification schemes.